2019
DOI: 10.1155/2019/8710180
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of an Evolutionary Young miR-1290 in an iPSC-Derived Neural Stem Cell Model of Autism Spectrum Disorder

Abstract: The identification of several evolutionary young miRNAs, which arose in primates, raised several possibilities for the role of such miRNAs in human-specific disease processes. We previously have identified an evolutionary young miRNA, miR-1290, to be essential in neural stem cell proliferation and neuronal differentiation. Here, we show that miR-1290 is significantly downregulated during neuronal differentiation in reprogrammed induced pluripotent stem cell- (iPSC-) derived neurons obtained from idiopathic aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…More recently, this increase in GABAergic neurons but not glutamatergic neurons, has been partially replicated from non-macrocephalic individuals with ASD, finding an increase in GABAergic cell markers, but no long-term changes in glutamatergic cell markers [117]. Yet, another study found a decrease in the total number of neurons in cultures from individuals with ASD without macrocephaly [118]. Contrary to the studies above which found some changes in cell proportions, a study performed using iPSCs from individuals with idiopathic ASD [116] found no change in cell proportions, but rather observed a reduction in glutamatergic synaptogenesis.…”
Section: Neuronal Differentiation and Morphologymentioning
confidence: 91%
See 2 more Smart Citations
“…More recently, this increase in GABAergic neurons but not glutamatergic neurons, has been partially replicated from non-macrocephalic individuals with ASD, finding an increase in GABAergic cell markers, but no long-term changes in glutamatergic cell markers [117]. Yet, another study found a decrease in the total number of neurons in cultures from individuals with ASD without macrocephaly [118]. Contrary to the studies above which found some changes in cell proportions, a study performed using iPSCs from individuals with idiopathic ASD [116] found no change in cell proportions, but rather observed a reduction in glutamatergic synaptogenesis.…”
Section: Neuronal Differentiation and Morphologymentioning
confidence: 91%
“…Neuronal cultures from individuals with idiopathic ASD and macrocephaly displayed accelerated cell cycle progression, accompanied by upregulation of genes involved in cell proliferation in several independent studies, making this one of the few findings to have been replicated [59,60,117,119]. Two studies also found that neurons derived from individuals with ASD but without macrocephaly also proliferated faster [118,120]. Conversely, genetically defined forms of ASD, mutation in NRXN1, and 22q11.2 deletion showed evidence of a decreased proliferation rate [124,135,144].…”
Section: Cell Cycle and Proliferationmentioning
confidence: 93%
See 1 more Smart Citation
“…Deletion of one copy of these genes should result in a 1.5 to 2-fold Fig. 3 Examples of studies utilizing iPSC models to study nonsyndromic idiopathic ASD [18,34,[49][50][51][52][53][54][55][56]. Studies are ordered by year with the most recent at the top and include the total number of XX and XY patient iPSCs used in the bar chart reduction in gene expression.…”
Section: An Ideal Scenariomentioning
confidence: 99%
“…Of note, from the studies of nonsyndromic idiopathic ASD using iPSC lines discussed above in Fig. 3, only one study used iPSCs from a public repository [49] and the remaining were reprogrammed by individual laboratories, suggesting that public repositories are not yet widely utilized in published ASD studies. It is therefore important to ascertain whether this is for historic reasons (e.g., laboratories initiated studies prior to the availability of relevant iPSCs) or whether aspects of existing ASD collections do not meet study needs (e.g., laboratories reprogramed their own samples because of a need for phenotyping data not found in current repositories).…”
Section: Regulatory Considerations For Hpsc Collectionsmentioning
confidence: 99%